Teaching for intelligence what schools can do - Gerbracht, Molly; Ryan, Susan; Cosenze, John M. (Illinois : SkyLight Training and Publishing, 1998)
Teaching for intelligence : What schools can do, a town hall meeting in which the nation's leading experts will address issues regarding intelligence in schools
Editor, John M. Cosenze
Keywords: Thought and thinking -- Study and teaching; Teaching; Intelligence